Promotion of The Human Skeletal Heritage: A Milanese Perspective (LANX. Journal of the Scuola di Specializzazione in Beni Archeologici - Università degli Studi di Milano, 2015)
The history and cultural heritage of a city can be evaluated not only through the study of the works of art, artifacts or buildings, but also through the examination of the remains of persons who walked the city in the past millennia. Therefore several thousands of skeletal remains found in Lombardia, especially in Milano, act as cultural assets, though in an the ethical scenario of full respect of human remains. In this way the skeletons tell a history concerning the conditions of health, the richness, culture and even violence, which may confirm, integrate or deny the historical sources when available. Preliminary studies performed on skeletons from different areas of Lombardia have already demonstrated the potential of skeletal material in highlighting for example the evolution of infectious diseases from the Roman age to the Middle Ages, the multiethnicity of Milan at the time of St Ambrose, the heavy labor of children which seems to be present among the Longobards who inhabited the geographic areas of Bergamo as well as Manzoni’s plague affecting the remains found under the Spanish walls. How were they different from us for what concerns life expectancy, diseases, interpersonal violence and lifestyle? In this the skeleton comes through as a true cultural asset.
Keywords: history; anthropology; archaeology; cultural asset; Milan; Lombardia